Implementasi Traveller Game Learning Untuk Meningkatkan Hasil Belajar Dan Keterampilan Sosial Siswa - Eko Prasetyo Utomo (Jurnal Lingkar Mutu Pendidikan, 2021)
This study aimed to: 1) the implementation of Traveler Game Learning assisted by the media Jelajah Nusantara; 2) improving students' cognitive learning outcomes; and 3) improving students' social skills. This research method uses Classroom Action Research (CAR). The results of this study indicate an increase in three aspects, namely aspects of the quality of learning by teachers, aspects of student cognitive learning outcomes and aspects of social skills.The quality of learning by teachers increased from 85.71% in the cycle I to 91.42% in cycle II. Mastery of students' cognitive learning outcomes classically increased from 76.67% in cycle I to 90% in cycle II. The quality of students' social skills increased from 79.05% in cycle I to 90% in cycle II. Based on these conclusions, the use of traveler learning games can be used as an alternative in social studies learning for the junior high school level